Strange Vices: Transgression and the Production of Difference in the Giallo (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
The giallo, an Italian genre of horror film that peaked in the 1970s, is infamous for peddling shock and slaughter. Under the graphic sex and violence, however, the giallo expresses popular anxiety surrounding the transgression of social and sexual norms in modern Italy. Superficially, the giallo seems to suggest that social and cultural turmoil necessarily produces death. Yet the giallo foregrounds the obvious excitement and attraction of transgression, allowing that transgression could in fact be generative of positive, invigorating difference.
Keywords: giallo; horror movie; Italy; 70s